2008
DOI: 10.1111/j.1600-0897.2008.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Treatment with Tumor Necrosis Factor Inhibitors and Intravenous Immunoglobulin Improves Live Birth Rates in Women with Recurrent Spontaneous Abortion

Abstract: CitationWinger EE, Reed JL. Treatment with tumor necrosis factor inhibitors and intravenous immunoglobulin improves live birth rates in women with recurrent spontaneous abortion. Am J Reprod Immunol 2008; 60: 8-16 doi:10.1111/j.1600-0897.2008 Problem The purpose of this study was to investigate whether treatment with tumor necrosis factor (TNF) inhibitors combined with intravenous immunoglobulin (IVIG) increases live birth rates among women with recurrent spontaneous abortion (RSA) concurrently treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 31 publications
(26 reference statements)
2
114
0
4
Order By: Relevance
“…Indeed, a recent study showed that treatment with TNF-a inhibitors and i.v. Ig may improve live birth rates in women who suffer recurrent pregnancy loss (57).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study showed that treatment with TNF-a inhibitors and i.v. Ig may improve live birth rates in women who suffer recurrent pregnancy loss (57).…”
Section: Discussionmentioning
confidence: 99%
“…In women who suffer habitual abortion, there is no elevation of sTNF-R1 and sTNF-R2 levels during pregnancy [30]. Treatment with inhibitors of tumor necrosis factor and intravenous immunoglobulin was found to improve live birth rates in women with habitual abortion [31].…”
Section: Etanerceptmentioning
confidence: 99%
“…So far, the recommendations per observational studies are that women of childbearing age with autoimmune diseases should ideally plan to conceive when their disease is well controlled and while on no medication, and most pregnant patients can discontinue their anti-TNFα treatment early in pregnancy without increasing maternal and fetal risks. 197 Anti-TNFα treatment has been shown to increase live birth rates in women with recurrent spontaneous abortion 67 and in a subset of patients with a history of .2 failed in-vitro fertilization attempts, 200 with the latter study having an impressive 100% pregnancy and 88% take-home baby rate. In both of the cohort-controlled, non-randomized studies, treatment was generally started a month prior to starting a cycle of conception, and continued until a fetal heart was demonstrable by ultrasound.…”
Section: Tnfα-inhibitors and Their Role In Pregnancymentioning
confidence: 99%
“…Although the observational studies of Winger et al represent important new data in the field of reproductive immunology, 67,200,202,203 further prospective randomized controlled studies are needed. Studies in mice are showing that targeting placental TNFα using TNFα-antagonists such as etanercept prevents fetal hypoxia and neuroproliferative defects in the fetal brain.…”
Section: Tnfα-inhibitors and Their Role In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation